Hubungan Daya Terima Makanan dengan Tingkat Konsumsi Energi dan Protein Santriwati - Hesti Atasasih; Alkausyari Aziz (Jurnal Kesehatan Komunitas, 2022)
ABSTRACT Adolescent nutritional intake needs considered, especially those school in boarding, so that it can affect their food intake. Research objective was to determine relationship between food acceptance and level of energy and protein consumption of students. This study used a cross sectional study with quantitative approach. Population and research sample were students of VII and VIII grade Ummahatul Mukminin Islamic boarding school. Data were processed using SPSS version 25.0 for Windows. Results showed the students acceptance of food served was in moderate category, the average energy requirement students was 1754.58 kcal/day, while protein needs of 51.79 g/day, most of the energy and protein consumption levels of students were in normal category, All of the students energy and protein availability in normal category, students consumption level of energy and protein needs in weight deficit category, level availability of santriwati's energy and protein needs in deficit category. The conclusion of study is a significant relationship between food acceptance and level of energy and protein consumption students. Keywords : Acceptability, Level of Energy and Protein Consumption, Santriwati